“PSYCHOLOGY OF YOUNG SCHOOL AGE CHILDREN” (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: The article provides information on the development of psychological characteristics of children of primary school age. In particular, the article covers information on the psychological changes that occur in children of primary school age during their preparation for school.